Modulating Ferroptosis in Aging: The Therapeutic Potential of Natural Products - Sherif Hamidu; Seth Kwabena Amponsah; Abigail Aning; Latif Adams; Justice Kumi; Eunice Ampem-Danso; Fatima Hamidu; Mustapha Abdul Mumin Mohammed; Gabriel Tettey Ador; Sanjida Khatun (Journal of Aging Research, 2025)
Aging is a multifactorial process driven by accumulating cellular damage. Ferroptosis—an iron-dependent, lipid peroxidation-mediated form of cell death—has emerged as a critical contributor to age-related tissue degeneration. This review synthesizes current evidence linking ferroptosis to key aging hallmarks, including oxidative stress, chronic inflammation, mitochondrial dysfunction, and dysregulated iron metabolism. Central to these interactions is the age-associated decline in antioxidant defenses (e.g., glutathione, glutathione peroxidase 4 [GPx4]) and paradoxical iron dynamics, where systemic deficiency coexists with intracellular overload, promoting reactive oxygen species (ROS) generation via the Fenton reaction. Natural products such as resveratrol, curcumin, and epigallocatechin gallate (EGCG) exhibit promising anti-ferroptotic effects through mechanisms including iron chelation, ROS scavenging, and upregulation of endogenous antioxidants. Preclinical and clinical studies indicate their potential in reducing lipid peroxidation and enhancing cellular resilience in aging contexts. However, challenges such as poor bioavailability and tissue-specific iron dysregulation remain. This review explores how combinatorial approaches—targeting multiple ferroptosis pathways—may offer synergistic therapeutic benefits. Collectively, ferroptosis inhibition emerges as a promising strategy to mitigate age-associated tissue damage and promote healthy aging.